In-vitro Anthelmintic activity of Smilax myosotiflora Plant (locally known as Ubi Jaga) Extracts Against Haemonchus contortus Worms in Goats - A. Rahman, Wahab; Yong, Chow Fatt; Sulaiman, Shaida Fariza (Malaysian Journal of Science, 2010)
This study was conducted to evaluate the in-vitro anthelmintic activity of Smilax myosotiflora plant (locally known as ubi jaga) extract against third-stage Haemonchus contortus larvae from goats. Two trials were conducted, whereby each trial followed similar protocols in which Smilax leaves were extracted using methanol solution. The larvae were than tested with different concentrations of the extract. Smilax plant extract was effective against worm larvae in goats. A 100% mortality had been achieved at 5 mg/ml of concentration. (Keywords: in-vitro, Smilax myosotiflora, Haemonchus contortus, goats)